Inter- and intra-individual variation in urinary concentrations of parabens in male and female Japanese subjects. Issue 1 (2nd January 2018) - Nishihama, Yukiko; Ameda, Reika; Yoshinaga, Jun; Konishi, Shoko; Yoneyama, Miyuki; Nakajima, Daisuke; Shiraishi, Hiroaki; Imai, Hideki
ABSTRACT: We evaluated the representativeness of concentrations of parabens in a spot urine sample for the assessment of long-term exposure levels. Urine sample was taken monthly from 10 male Japanese subjects (35.9 ± 6.8 years) and 12 female Japanese university students (21.1 ± 0.4 years) for 5 months and measured for methyl (MP), ethyl (EP), propyl (PP) and butyl (BP) parabens by liquid chromatography–tandem mass spectrometry. Median (min–max) specific-gravity-adjusted urinary concentrations of the male group ( n = 10) were 39.7 (2.99–268), 1.69 (< 0.045–75.2), 0.569 (< 0.11–123) and 0.0264 (< 0.020–24.4) ng mL −1 for MP, EP, PP and BP, respectively. Those of the female group ( n = 12) were 283 (5.49–1687), 9.30 (0.290–487), 22.9 (< 0.11–307) and 3.76 (< 0.020–135) ng mL −1, respectively, which were significantly higher than those of the male group. Intra-class correlation coefficients (ICCs) were calculated for the four parabens to find 0.56, 0.58, 0.39 and 0.28 for MP, EP, PP and BP, respectively, in the male group, and 0.40, 0.43, 0.41 and 0.37 for MP, EP, PP and BP, respectively, in the female group. The results suggested that four paraben concentrations in a spot urine sample moderately reflected long-term paraben exposure of Japanese subjects. Source of exposure to parabens is also discussed.